The Escherichia coli cysG gene encodes S-adenosylmethionine-dependent uroporphyrinogen III methylase. - Warren, M J (1990)
The Escherichia coli cysG gene was successfully subcloned and over-expressed to produce a 52 kDa protein that was purified to homogeneity. This protein was shown to catalyse the S-adenosylmethionine-dependent methylation of uroporphyrinogen III to give a product identified as sirohydrochlorin on the basis of its absorption spectra, incorporation of 14C label from S-adenosyl[Me-14C]methionine and mass and 1H-n.m.r. spectra of its octamethyl ester. Further confirmation of the structure was obtained from a 14C-n.m.r. spectrum of the methyl ester produced by incubation of the methylase with uroporphyrinogen III, derived from [4.6-13C2]porphobilinogen, and S-adenosyl[Me-13C]methionine.